2016
DOI: 10.3758/s13414-016-1068-9
|View full text |Cite
|
Sign up to set email alerts
|

Age matters: The effect of onset age of video game play on task-switching abilities

Abstract: Although prior research suggests that playing video games can improve cognitive abilities, recent empirical studies cast doubt on such findings (Unsworth et al., 2015). To reconcile these inconsistent findings, we focused on the link between video games and task switching. Furthermore, we conceptualized video-game expertise as the onset age of active video-game play rather than the frequency of recent gameplay, as it captures both how long a person has played video games and whether the individual began playin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In this vein, our finding of significant positive effects of bilingualism on verbal working memory among older children (age 7) suggests that working memory, relative to the inhibitory and shifting aspects of EF, likely requires more extensive bilingual experience to manifest. Given that cognitive processes vary in terms of malleability (e.g., Hartanto et al., ), various cognitive processes may not be similarly sensitive to the same extent of bilingual experience. Further research is necessary, therefore, to determine the mechanisms that underlie bilingual advantages in verbal and nonverbal working memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this vein, our finding of significant positive effects of bilingualism on verbal working memory among older children (age 7) suggests that working memory, relative to the inhibitory and shifting aspects of EF, likely requires more extensive bilingual experience to manifest. Given that cognitive processes vary in terms of malleability (e.g., Hartanto et al., ), various cognitive processes may not be similarly sensitive to the same extent of bilingual experience. Further research is necessary, therefore, to determine the mechanisms that underlie bilingual advantages in verbal and nonverbal working memory.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research has demonstrated that a group of adaptive, goal‐oriented control processes―inhibition, shifting, and updating of working memory (Miyake et al., )―collectively known as executive functions (EF) are essential for many crucial aspects of childhood development, including school readiness (Blair, ), future academic achievement (Bull, Espy, & Wiebe, ), socioemotional competencies (Broidy et al., ), and physical health (Riggs, Chou, Spruijt‐Metz, & Pentz, ). In view of the predictive role EF plays in early childhood, scholarly interest in the childhood experiential factors that modulate children's executive functioning has surged (e.g., Diamond, ; Hartanto, Toh, & Yang, ). Two of these experiential factors are socioeconomic status (SES; e.g., Farah et al., ; Mezzacappa, ) and bilingualism (e.g., Hartanto & Yang, ; Yang & Yang, ).…”
mentioning
confidence: 99%
“…NVGP, on the other hand, reported to have played either no AVG or no video games at all during the last 6 months. Recently, Hartanto, Toh, and Yang () found that the age of active onset of video game playing better predicted performance in a cognitive control task than did recent playing. In sum, future studies should emphasize a more fine‐grained classification by taking into account different subgroups of VGP and NVGP as well as recent and previous video game playing (especially during periods of high cognitive plasticity).…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic since, in some cases, cognitive changes have been found after just a few weeks of VG training. However, in most cases, the onset age of active VG play, which is a particularly relevant aspect (Hartanto et al, 2016), is not taken into account. Another relevant variable, which tends to be forgotten, is lifetime VG experience, usually measured in hours.…”
Section: Limitationsmentioning
confidence: 99%